1992
DOI: 10.1002/1097-0142(19921201)70:11<2624::aid-cncr2820701110>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase combination chemotherapy in small cell lung cancer. A phase II study

Abstract: Background and Methods. Fifty‐one patients with small cell lung cancer (SCLC) were treated with alternating urokinase (UK)‐cyclophosphamide‐doxorubicin (Adriamycin, Adria Laboratories, Columbus, OH)‐vincristine and cisplatin‐etoposide‐vincristine. UK was given as a loading dose of 3000 μg/kg body weight, followed by 3000 μg/kg/h for 6 hours. Thoracic irradiation with split technique (46 Gy) and prophylactic cranial irradiation (25 Gy) were administered to responding patients. A second staging was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The clinical use of anti-coagulants and fibrinolytic therapies in cancer patients has been reported before (4145). These studies have shown that administration of anti-coagulants such as heparin and warfarin improve mean survival in patients with small cell lung cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The clinical use of anti-coagulants and fibrinolytic therapies in cancer patients has been reported before (4145). These studies have shown that administration of anti-coagulants such as heparin and warfarin improve mean survival in patients with small cell lung cancer.…”
Section: Discussionmentioning
confidence: 94%
“…The rationale presented for the use of anti-coagulants is that it reduces the occurrence of spontaneous thromboembolism and tumor cell dissemination (44, 46). Some studies have reported the beneficial effects of using urokinase in conjunction with chemotherapy (41). The mechanism for the improved response to chemotherapy was not explored, however.…”
Section: Discussionmentioning
confidence: 99%
“…94,96 Experimental and clinical studies suggest that heparin and vitamin K antagonists are effective compounds for the prevention of metastases. 33,107 Data from randomised trials suggest that small-cell lung cancer (SCLC) consistently responds to heparin and vitamin K antagonist, but several other tumors, including non small-cell cancer (NSCLC), colon and prostate cancer, do not respond to warfarin 13,11,55,111,117 and do not produce thrombin. 118 Further studies are needed to confirm the existing data and to determine whether haparin, vitamin K antagonists or platelet aggregation inhibitors effectively prevent the formation of metastatic tumors.…”
Section: Role Of a Nticoagulants And I Nhibitors Of P Latelet A Ggregmentioning
confidence: 99%
“…Several studies have suggested that anticoagulant therapy may improve survival in patients with SCLC [7]. Specifically, improved SCLC disease outcome has been observed in randomized clinical trials (RCTs) of warfarin [8,>9] and unfractionated heparin [10], and in a Phase II study of urokinase [11]. However, further clinical studies are needed to define the role that anticoagulants will play, if any, in the treatment of SCLC and other tumor types.…”
Section: Introductionmentioning
confidence: 99%